Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi Pada Pegawai di Instalasi Gizi RS Jantung dan Pembuluh Darah Harapan Kita - Fauziyati, Rizka Akbar; Indriasari, Marina (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2024)
Background: Hypertension is a condition where blood pressure increases beyond normal limits. Hypertension is a non-communicable disease which is the cause of high death rates in Indonesia. One of the factors that causes hypertension in sufferers includes the nutritional status of obesity and sodium consumption habits. Objective: This research is to determine the factors associated with the incidence of hypertennis in employees at the Nutrition Installation of Harapan Kita Heart and Blood Vessel Hospital. This research uses an observation method with a cross sectional design. Method: The sampling technique used simple random sampling with a sample size of 57 respondents. Hypertension data was obtained through blood pressure measurements, characteristics data and nutritional status data through questionnaires, data on sodium consumption habits was obtained through a semi-quantitative food frequency questionnaire form. This research uses the Chi-square statistical test with a p-value (<0.05). Results: It was found that 21 respondents (36.8%) had hypertension. Based on the Chi-square test, a value of p=0.002 was obtained for the obesity nutritional status variable, p=0.409 for the variable sodium consumption habits. Conclusion: there is no significant relationship between sodium consumption habits and the incidence of hypertension (p>0.05). However, there is a significant relationship between obesity nutritional status and the incidence of hypertension (p<0.05).